Mathematical Model of a Constructal Coanda Effect Nozzle - Michele Trancossi; Jill Stewart; Maharshi Subash; Diego Angeli (Journal of Applied Fluid Mechanics, 2016)
This paper analyses the ACHEON Coanda effect nozzle for aircraft propulsion, based on the dynamic equilibrium of two jet streams. The ACHEON concept, and, in particular, the HOMER nozzle, which is its main component, are presented, together with the literature milestones from which the idea originally stems. A sub-system analysis inspired by the principles of Constructal Theory is presented for the current architecture. A mathematical model of a 2D case of the system is developed, focusing on the combined effect of the mixing of the two streams and the Coanda adhesion over a convex surface. A validation of the model is also reported, based on 2D CFD analyses, under the hypothesis of incompressible flow. Results highlight that, in spite of its relative simplicity, the model produces accurate results.